Teaching Excellence in Higher Education : Challenges, Changes and the Teaching Excellence Framework. - French, Amanda (Emerald Publishing Limited, 2017)
This book offers inter-disciplinary, evidence-informed discussion around notions of excellence in higher education teaching. It will act as a key stimulus for institutional and sector-wide debates and a reference point for initiatives around the TEF agenda.
Keywords: College teaching.; Education, Higher.; Effective teaching.; elektronické knihy; electronic books